Ethanol treatment improves the sensory quality of cherry tomatoes stored at room temperature. (15th November 2019) - Liu, Haoran; Meng, Fanliang; Chen, Shanshan; Yin, Tingting; Hu, Songshen; Shao, Zhiyong; Liu, Yuanyuan; Zhu, Changqing; Ye, Hongxia; Wang, Qiaomei
Highlights: Ethanol treatment influenced the softening of cherry tomato fruits. Ethanol treatment improved ascorbic acid content in cherry tomato. Ethanol treatment enhanced sucrose, fructose and favorable volatiles in cherry tomato. Selected consumers showed a preference to ethanol-treated cherry tomato fruits. Abstract: The effects of ethanol treatment on quality characteristics of cherry tomatoes were investigated over 11 days of storage at room temperature (25 °C). Results showed that sensory quality was improved after ethanol treatment, with redder, softer fruits at the edible stage (11 days) compared with control fruit. In addition, the contents of ascorbic acid, sucrose and fructose were elevated after ethanol treatment as well as the concentration of 6-methyl-5-hepten-2-one. Conversely, decreased levels of methyl salicylate (MeSA), guaiacol, (Z)-3-hexenal and (E)-2-hexenal were observed. Selected consumers showed a preference for ethanol-treated cherry tomato fruits compared with controls. Taken together, 0.1% ethanol application has the potential to improve the quality characteristics of cherry tomatoes stored at room temperature.